2019
DOI: 10.1371/journal.pcbi.1006952
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of VRC01 neutralization sensitivity by HIV-1 gp160 sequence features

Abstract: The broadly neutralizing antibody (bnAb) VRC01 is being evaluated for its efficacy to prevent HIV-1 infection in the Antibody Mediated Prevention (AMP) trials. A secondary objective of AMP utilizes sieve analysis to investigate how VRC01 prevention efficacy (PE) varies with HIV-1 envelope (Env) amino acid (AA) sequence features. An exhaustive analysis that tests how PE depends on every AA feature with sufficient variation would have low statistical power. To design an adequately powered primary sieve analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 82 publications
(97 reference statements)
3
31
0
Order By: Relevance
“…Buiu et al presented a trained neural network approach to directly predict IC50 values of given antibodies against HIV-1, based on the Env sequence information (31), and Hake et al built binary classifiers with nonlinear support vector machines and string kernels to distinguish between HIV-1 resistance and susceptibility to a bNAb based on different Env amino acid (AA) sequences (20). More recently, Magaret et al used 2 machine-learning approaches, based on a set of predefined AA sequence features to predict several TZM-bl neutralization assay outcomes for the CD4bs antibody VRC01, including virus's resistance versus sensitivity status, logIC50/80 values, and estimated neutralization slope of the dose-response curves (22). Bricault et al used random forest for IC50 regression predictions that included information on AA, PNGS, clade, and variable loop characteristics, demonstrating that the model accuracy using all the information was superior compared with model accuracy including single parameters, i.e., contact-region-only signatures (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buiu et al presented a trained neural network approach to directly predict IC50 values of given antibodies against HIV-1, based on the Env sequence information (31), and Hake et al built binary classifiers with nonlinear support vector machines and string kernels to distinguish between HIV-1 resistance and susceptibility to a bNAb based on different Env amino acid (AA) sequences (20). More recently, Magaret et al used 2 machine-learning approaches, based on a set of predefined AA sequence features to predict several TZM-bl neutralization assay outcomes for the CD4bs antibody VRC01, including virus's resistance versus sensitivity status, logIC50/80 values, and estimated neutralization slope of the dose-response curves (22). Bricault et al used random forest for IC50 regression predictions that included information on AA, PNGS, clade, and variable loop characteristics, demonstrating that the model accuracy using all the information was superior compared with model accuracy including single parameters, i.e., contact-region-only signatures (21).…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution imaging approaches have revealed that bNAb and glycan interactions are common across all bNAb classes, and previous analyses to map antibody binding and antibody neutralization activity depended not only on sequence, but also on glycan occupancy (18,19). Computational approaches for prediction of neutralization sensitivity based on Env sequences have been reported previously (20)(21)(22). Information of glycans and glycan occupancy, however, have not been included in these models, therefore excluding a critical component.…”
Section: Introductionmentioning
confidence: 99%
“…While phenotyping the bnAb sensitivity of patient viruses can be performed using either bulk or limiting dilution T cell outgrowth cultures, these assays can be labor intensive, costly, and may fail to detect minor pre-existing resistant variants ( 65 , 66 ). An alternative strategy for future development may be to use predictive modeling based on env sequencing of the patient’s quasispecies to determine bnAb sensitivity patterns and optimize combination cocktails ( 67 69 ).…”
Section: Combinations Of Bnabsmentioning
confidence: 99%
“…These algorithms have become more powerful in predicting epitopes and can be combined to increase the accuracy of large-scale peptide epitope predictions in HIV. For example, Bricault et al [13] recently demonstrated that bnAbs signatures can be used to engineer HIV-1 Env vaccine immunogens capable of eliciting Ab responses with greater neutralization breadth by a machine-learning-based prediction approach [13,14]. The second strategy is in vitro toward the discovery of new epitopes by a phage display technology, resulting in the expression of a peptide that mimics the structure of an epitope.…”
Section: Strategies For Peptide Mappingmentioning
confidence: 99%